(untitled) (International Journal of Applied Research in Management and Economics, 2022)
In today’s environment the leader is already faced with changes in the status quo of the field of work. Changes such as automation and digitization of work, changing forms of employment and the constant demand for further specialization make up an explosive context that could not easily be considered productive and psychologically likable for humans. There has been a great demographic shift, therefore different generations of employees need to be led properly within the organization. On the threshold of the 4.0 industrial revolution, leaders need to balance variables such as technological advances and the generational differences and/or clashes. To properly lead the organization, leaders must have abilities and skills that fall within all four capitals, economic, human, social and positive psychological capital. The ever-evolving theory of leadership highlights the characteristics that leaders must have for the organization to prosper and subordinates/followers as well. The paper discusses the leadership theory and the emergence of e-leadership. The new mentality and the differences within different generations are analyzed as well. The paper proposes the concept of the ‘holistic’ leader and discusses the gap regarding the leadership theories and the need for the higher education programs to be modified for the new leaders to be trained more effectively.